If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9(1d-4)-8=5d
We simplify the equation to the form, which is simple to understand
9(1d-4)-8=5d
Reorder the terms in parentheses
+(+9d-36)-8=5d
Remove unnecessary parentheses
+9d-36-8=+5d
We move all terms containing d to the left and all other terms to the right.
+9d-5d=+36+8
We simplify left and right side of the equation.
+4d=+44
We divide both sides of the equation by 4 to get d.
d=11
| f(t)=-16t^2+16T+10 | | (X)+(x+1)+(x+2)=168 | | 6f+9g=3g | | -5(n+6)-7= | | 8t-15=8t+3 | | 3x-11=3x+1.5 | | -100=5(5x-5) | | -7k+4+5k= | | 6x^2+3x-320=0 | | 0=-16t^2+16t+10 | | 6(1c+4)=4c-18 | | -0.39x^2+5.6x=0 | | X+(x+1)=571 | | 7m-6m=8 | | -2p+5=16 | | x^2-12x+80=125 | | y+1/4=0.75 | | 3(2+x^2)=29-2(4+x^2) | | 17*4.65= | | y+1/4= | | 8-4n=44 | | 8u+4=20 | | 7v^2=61v-40 | | X-5z=-2 | | 0.02x+0.2x=1 | | y-4=4(x+1) | | -.5(x+9)+5.75x=0.375x | | -x^2+1x+0.41=0 | | g(x)=2x^2+4x+12 | | 2x^2-6=2 | | n-(-13)=29 | | 6x=173 |